Baosteel Group : seeking strategic synergy through M&A integration - Xu, Jingyue, active 2016 (London : Renmin University, 2016)
As the most competitive iron and steel enterprise in China, Baosteel Group defined its strategy as "quality product plus scale economy" and has developed very fast since 2006. The basic developing model of Baosteel Group can be described as "expanding the scale by M&A," improving overall competitiveness by effective integration. This case analyzes two successful M&A cases of Baosteel-Bayisteel and Ningsteel; introduces their processes of M&A and integration thoroughly; and demonstrates the distinctive mode of Baosteel's M&A integration based on strategic synergy.
Originally Published InXu, J. (2017). Baosteel Group: Seeking Strategic Synergy through M&A Integration. Beijing, China: Renmin University Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bao gang ji tuan gong si -- Case studies; Consolidation and merger of corporations -- Case studies